Implementasi Model Pembelajaran Blended Learning terhadap Motivasi Belajar Ekonomi Peserta Didik Pada Masa Pandemi COVID-19 - Rahmatullah Rahmatullah; Muhammad Hasan; Muhammad Ihsan Said Ahmad; Andi Tenri Ampa; Nur Arisah (Indonesian Journal of Learning Education and Counseling, 2021)
Indonesia is faced with an outbreak of the COVID-19 virus in early 2020. The COVID-19 pandemik has an impact on Indonesia, especially for the world of education, where the learning process is transferred to the online learning system (online) and remains at home to take part in the learning process. One of the learning models used for the learning process is the blended learning model. This study is designed to reveal the effect of the blended learning model on students' economic learning motivation and the effect of the blended learning model on the COVID-19 pandemik. This study was conducted using a phenomological method with a qualitative approach. The population in this study took proportional random sampling of information so that 16 informants were obtained consisting of 5 students (i) at the Makassar State University (UNM), 5 high school students (SMA) scattered in several cities, and 6 students from Junior High Schools (SMP) from several cities. Data collection techniques used in this study were online interviews via the WhatsApp application with several questions and data analysis techniques used to assist this study were coding techniques. Based on the research results, it can be seen that (1) the blended learning model has a positive effect on economic learning motivation in students (2) the blended learning model has a positive effect on the COVID-19 pandemik period.